2005
DOI: 10.1081/css-200056912
|View full text |Cite
|
Sign up to set email alerts
|

Irrigated Alfalfa Response to Phosphorus and Potassium in a Calcareous Soil

Abstract: The response of alfalfa (Medicago sativa L.) to phosphorus (P) and potassium (K) fertilizer often varies with soil type, the initial soil test P and K levels, irrigation and harvest management, and yield level. The objectives of this study were to determine the response of irrigated alfalfa to P and K fertilizer on a Wetherill loam soil in southwestern Colorado and to assess the impact on soil test P and K levels. Four P (0, 37, 74, and 148 kg ha 21 ) by three K (0, 93, and 186 kg ha 21 ) rates were applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…1). As frequently reported, alfalfa yields depend on the K e content of the soils (Kafkafi et al, 1977; Havlin et al, 1984; Berrada and Westfall, 2005).…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…1). As frequently reported, alfalfa yields depend on the K e content of the soils (Kafkafi et al, 1977; Havlin et al, 1984; Berrada and Westfall, 2005).…”
Section: Resultsmentioning
confidence: 64%
“…In the irrigated areas of the Ebro valley (Spain), the normal K e contents for a good crop are considered to be between 125 and 250 mg kg −1 , whereas levels below 125 mg kg −1 are considered low (Piñeiro et al, 2010). According to Berrada and Westfall (2005), the response of alfalfa to K and P often varies with growing conditions, soil type, initial soil test K and P levels, irrigation, harvest management, and yield level. Havlin et al (1984), in Colorado, reported that when soil test K levels remained high, no K fertilization was necessary unless there would be a direct economic benefit from improved alfalfa forage quality.…”
mentioning
confidence: 99%
“…These values would yield an annual removal of P on the order of 9.9 kg ha -1 in a single harvest. Phosphorus concentrations over a 3-year period in irrigated pure alfalfa stands have been reported by Berrada and Westfall (2005) to average 2.4 g kg -1 for a range in P additions. Marino and Berardo (2005) found a 4-year, cumulative removal of P by alfalfa, to total 61 kg ha -1 without any direct addition of P. This is approximately three times the amount removed in the alfalfa cover type over a similar time frame, but it should be noted that the alfalfa cover type in the current study was strongly dominated by smooth brome by the 4th year of the study.…”
Section: Discussionmentioning
confidence: 98%
“…Phosphorus (P) is one of the nutrients that have a major inf luence on the growth of alfalfa because of its need in different biochemical functions of the plant and, its deficiency reduces the amount and quality of forage (Picone et al, 2003;Mikkelsen, 2004). Alfalfa shows significant response to increased application rates of P (Berrada and Westfall, 2005). This nutrient is added to the soil in a single application at the beginning of the cycle, regardless of the irrigation system used and the number of cuts made in alfalfa forage (Karagić et al, 2008).…”
Section: Materiales Y Métodosmentioning
confidence: 99%